A luta contra a desesperança: a experiência de gestantes com HIV - Oliveira, Fernanda Ferreira Damaceno (Universidade Federal de São Carlos, 2013)
The discovery of the Human immunodeficiency virus (HIV) during pregnancy drives woman to experience prejudice, discrimination and the possibility to infect her child, promoting an existential reflection. Suffering is present, conducting to a hope experience. Hope is a dynamic and multidimensional process, focused in the possibility to achieve what is desired. Incorporate bases and force to exist, being reached in the moments of difficulty. Therefore, the routine with HIV during pregnancy connect itself to the experience of hope, for that reason the present study has hope as its component. The objective was to explore and describe hope experiences during pregnancy of woman that discovery her HIV seropositive at prenatal. This study had as theoretical reference the Symbolic Interactionism and narratives research as methodological reference. The strategy to data collection was semi-structured interview associated with hope s genogram and ecomap. It was part of this study seven pregnant women who discovered their HIV seropositivity during prenatal. The results are present and organized in the following thematic units: Life review ; be a mother , care of herself , surrender to divine intervention , social interaction and hope . The main phenomenon identified was fight against the lack of hope . It was conclude that the tendency to lack of hope is strongly present in the gestational routine of these women and that exist interactions that are hope promoters and others that restrict it. Woman try to valorize those that are hope promoter to reach what It was established as a goal in that period: contribute with her child s seronegativity.
Keywords: Enfermagem; Gestação; HIV (vírus); Pesquisa qualitativa; Esperança; Mudança; Vida; Pregnancy; HIV; Qualitative research; Life change events; CIENCIAS DA SAUDE::ENFERMAGEM